Organizational behavior - Joseph E. Champoux (Thomson/South-Western, 2006)
ORGANIZATIONAL BEHAVIOR: INTEGRATING INDIVIDUALS, GROUPS AND ORGANIZATIONS, THIRD EDITION is a well-organized introduction to the current field of organizational behavior with in-depth coverage of the most critical concepts. Its practical approach shows the power of organizational behavior theory for understanding one's behavior and the behavior of others in any organization. Although firmly grounded in behavioral science theory and research, the text is not a compendium of research findings. Champoux includes examples and builds frameworks that make the material clear and easy to understand. The concise format allows the text to be used as a primer or to be supplemented with additional cases, readings, or exercises. More interactive than in previous editions, this text provides students with several online features to reinforce their knowledge of chapter content with exercises, practice and other learning opportunities